Internalization of Asy’ariyyah Creed Values through ‘Aqaidul Iman Learning - Abdul Kodir Alhamdani; Muhamad Ramdhan; Ramdani Wahyu Sururie; Syamsul Azizul Marinsah (Journal of Pesantren and Diniyah Studies, 2026)
Amidst the proliferation of transnational ideologies and the phenomenon of religious instant-ism in the digital era, the preservation of Ahlussunnah wal Jama’ah (Aswaja) theology requires a pedagogical approach rooted in local wisdom. This research investigates the internalization of Asy'ariyyah creed values at Pondok Pesantren Al-Hikamussalafiyah Cipulus, Purwakarta, specifically through the study of the book ‘Aqaidul Iman by KH. Adang Badruddin (Abah Cipulus). Using a qualitative field research method, data were collected through in-depth interviews, participant observation of sorogan and lalaran activities, and manuscript analysis. The study reveals that ‘Aqaidul Iman serves as a strategic instrument of vernacularization of theology, transforming the classical text Tijan ad-Darari into Sundanese nadham (poetry) written in Pegon script. The internalization process follows a holistic trajectory: the transformation stage via the bandongan method for cognitive understanding; the transaction stage via the lalaran (collective chanting) tradition for affective habituation; and the trans-internalization stage, where theological values manifest as humility (tawadhu) and social tolerance. The research concludes that integrating the author’s charismatic authority (Rabithah) with the mnemonic efficacy of the local language creates a robust theological fortress that effectively shields santri from radicalism and superficial religious understanding.